A Meta-Analysis of Enteral Nutrition and Total Parenteral Nutrition in Patients with Acute Pancreatitis - Heming Quan; Xingpeng Wang; Chuanyong Guo (Gastroenterology Research and Practice)
Objective. To analyze the effect of total parenteral nutrition (TPN) and enteral nutrition (EN) in patients with acute pancreatitis. Methods. Randomized controlled trials of TPN and EN in patients with acute pancreatitis were searched in NCBI and CBM databases and The Cochrane Controlled Trials Register. Six studies were enrolled into the analysis, and the details about the trial designs, characters of the subjects, results of the studies were reviewed by two independent authors and analyzed by STATA 11.0 software. Results. Compared with TPN, EN was associated with a significantly lower incidence of pancreatic infection complications (RR=0.556, 95% CI 0.436∼0.709, P=.000), MOF (RR=0.395, 95% CI 0.272∼0.573, P=.003), surgical interventions (RR=0.556, 95% CI 0.436∼0.709, P=.000), and mortality (RR=0.426, 95% CI 0.238∼0.764, P=.167). There was no statistic significance in non-pancreatitis-related complications (RR=0.853, 95% CI 0.490∼1.483, P=.017). However, EN had a significantly higher incidence of non-infection-related complications (RR=2.697, 95% CI 1.947∼3.735, P=.994). Conclusion. EN could be the preferred nutrition feeding method in patients with acute pancreatitis.